A cross‐sectional study on factors affecting the intention to quit smoking among female call centre employees - Hyunjin Oh; Sunjoo Boo (Nursing Open, 2023)
Abstract Aim This study aims to describe smoking related characteristics among female call centre employees in South Korea and identify the factors influencing intention to quit smoking in the next 6 months. Design This is a cross‐sectional study. Methods An anonymous online survey was conducted at three call centres of credit card companies in South Korea. Female employees with at least 6 months of experience (n = 115) who were currently smoking were included in this study. Results Overall, 20% of participants intended to quit within 6 months. Female call centre employees find it most difficult to resist the urge to smoke in negative mood situations. Factors affecting the quit intention were higher educational status, previous quit attempts lower perceived risk of craving and higher social support. Public Contribution Measuring and monitoring craving as perceived risk and providing social support can be useful for designing smoking cessation interventions in this population.